Conceptualizing Team Working Memory: Implications for Human-Automation Collaboration. (September 2021) - Miyake, Tina; Parker, Charles; Hall, Anna; Boring, Ronald
Interactions between humans and machines are becoming increasingly more complex and intelligent. Building accurate models of human and automation collaboration will require identification and appropriate measurement of constructs. In this paper, we review several studies on working memory and automation. We then propose that the construct of Team working memory must be validated against established benchmarks and distinguished from individual WM. A separate construct for Team working memory might have implications for automation.